Marco Antonio Michel (coord.). Procesos habitacionales en la ciudad de México. México : UAM : Sedue, 1988. 290 p. - Muñoz Contreras, María Elena (Estudios Demográficos y Urbanos, 1989)
MARCO A. MICHEL (coord.), Procesos habitacionales en la Ciudad de México, UAM, Sedue, México, 1988.